Navigating the Dinamics of Teacher Job Satisfication: Leadership, Supervision and Performance - Rachmadi , Denny; Yanto , Heri; Yanto , Heri; ., Sukestiyarno; Sutopo , Yeri (Journal of Ecohumanism, 2024)
This study explores the impact of principal leadership, supervisory supervision, and teacher work climate on teacher job satisfaction in Indonesia, with a focus on the mediating role of teacher performance and the moderating effect of work motivation. Using a comprehensive approach that encompasses primary, secondary, and high schools across diverse geographic and economic settings, the research aims to provide a nuanced understanding of how these factors interact to influence teacher satisfaction and performance. The findings reveal that principal leadership and teacher work climate significantly enhance teacher job satisfaction, with teacher performance acting as a critical mediator in these relationships. However, the study indicates no significant moderating effects of work motivation on the relationships examined. These results suggest that while effective leadership and a supportive work environment are essential for improving teacher satisfaction, further exploration of motivation's role is warranted. Educational institutions are encouraged to implement professional development initiatives and foster supportive leadership practices to enhance teacher well-being and effectiveness. This research contributes valuable insights to the literature on educational leadership and teacher job satisfaction.